Two new tiger beetle (Coleoptera, Carabidae, Cicindelitae) species from the Tucuman-Bolivian forest in the National Tariquia Reserve, Bolivia - Perger, Robert; Guerra, Fernando (Zootaxa, 2012)
Two new tiger beetle species from subhumid Tucuman-Bolivian forest in the National Tariquia Reserve in Tarija, Bolivia, are described and illustrated. Cylindera (Plectographa) yaguaree n. sp. is the first described Neotropical species in this genus that has setae over the complete elytral surface. Pseudoxycheila tucumana n. sp. closely resembles Pseudoxycheila andina Cassola, but is readily distinguished by spots on elytra longer than elytra width. These two new species are likely endemic to Tucuman-Bolivian forest and bring the known endemic forest tiger beetle fauna of this ecoregion to three species.